A Note on Temporary Supply Shocks with Aggregate Demand Inertia - Ricardo J. Caballero; Alp Simsek (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study optimal monetary policy during temporary supply contractions when aggregate demand has inertia and expansionary policy is constrained. In this environment, it is optimal to run the economy hot until supply recovers. Positive output gaps in the low-supply phase lessen the negative output gaps expected to emerge once supply recovers. However, the policy does not remain loose throughout the low-supply phase: The central bank undoes the initial interest rate cuts once aggregate demand gains momentum. If inflation also has inertia, the central bank still overheats the economy during the low-supply phase but gradually cools it down over time.
Keywords: E21; E32; E43; E44; E52; G12; 330; monetary policy; interest rates; temporary supply shocks; aggregate demand inertia; inflation; Taylor rule; divine coincidence; policy frontloading; momentum; output and inflation gaps; the Phillips curve; Covid-19